USING WORD WALL PICTURE IN TEACHING VOCABULARY TO THE AUTISM CHILDREN AT SEKOLAH LUAR BIASA NEGERI PEMBINA PROVINSI SULAWESI SELATAN SENTRA PK-PLK - Nur Asik; Amirah Humaerah (Universitas Islam Negeri Alauddin Makassar, 2016)
The objective of this research was to find out the effectiveness using word wall picture in Teaching Students’ Vocabulary at sekolah luar biasa negeri pembina provinsi Sulawesi Selatan SENTRA PK-PLK. This research used Pre-Experimental Design. This reseach involved 3 students, at Sekolah Luar Biasa Negeri Pembina Provinsi Sulawesi Selatan SENTRA PK-PLK. The independent variable of this research was (using word wall picture) and the dependent variable was (students’ vocabulary). The instrument of this research was a multiple choices test used in pre-test and post-test. The result of the data indicated that there was a significant difference between students’ pre test and post test. The mean score of posttest (91) was greater than the mean score of pre test (53.33). The standard deviation of posttest (4.89) was lower than the standard deviation of pre test (11.54). From t-test, the researcher found that the value of t-test (4.797) was higher than t-table (4.303) at the level of significance 0.05 with degree of freedom (df) =2.It means that the use of Word wall picture was effective to improve the students’ vocabulary at Sekolah Luar Biasa Negeri Pembina Provinsi Sulawesi Selatan SENTRA PK-PLK.